Exploring Household Waste Management Literacy - Sri Wahyuni , Ayu; Irma; Kamal M.Sallo, Andi; Darmansyah Arif , Safriadi (The SDGS Forum Communication, 2024)
This study reveals the serious challenges faced by the community in Lebani Village, particularly in the Nipa-Nipa Selatan hamlet, regarding household waste and garbage management. The lack of adequate waste disposal facilities often leads to indiscriminate dumping of trash, creating environmental and public health issues. To address this problem, the study proposes solutions focusing on enhancing household waste management literacy. The research methodology involved the active participation of students from the ST Fatimah Mamuju Institute of Health and Business during their Field Learning Practice (PBL), enabling data collection from the Posko V of Lebani Village, particularly the Nipa-Nipa hamlet, in December 2022. The findings reveal that the Lebani Village community tends to use waste management strategies involving temporary storage and disposal into rivers or the sea. However, this method is limited in capacity and efficiency and potentially pollutes the water, leading to blockages. Based on these findings, the study highlights the need for innovative strategies in waste management to achieve better efficiency and promote recycling. In conclusion, the government needs to pay special attention and support environmentally friendly waste management programs in Lebani Village. Enhancing household waste management literacy is also a key step in changing community behavior towards waste management. Thus, this research provides a framework for addressing waste management issues in rural villages, with the hope of improving overall environmental quality and community welfare.